Montaigne in France 1812–1852 - Frame, Donald M. 1911-1991 (Columbia University Press, 1940)
Examines the revival of Michel de Montaigne's influence, a significant philosopher during the French Renaissance, during the early 19th century. Discusses the embrace of Montaigne's views during this period, as a new interest around individual personality, ideas, and style developed
Description based on online resource; title from PDF title page (publisher's Web site, viewed 30. Apr 2019)
Keywords: Montaigne, Michel Eyquem de -- 1533-1592; Geschichte 1812-1852; BIOGRAPHY & AUTOBIOGRAPHY / Literary; Rezeption; Frankreich